2017
DOI: 10.1021/acs.energyfuels.6b03246
|View full text |Cite
|
Sign up to set email alerts
|

Flame Characteristics of CH4/H2 on a Jet-in-Hot-Coflow Burner Diluted by N2, CO2, and H2O

Abstract: To enhance the knowledge to the combination of oxy-fuel combustion and MILD (moderate or intense low-oxygen dilution) combustion, namely oxy-MILD combustion, the present article examines the effects of different diluents (i.e., N2, CO2, and H2O) on the flame characteristics of CH4/H2 blended fuel in a JHC (jet-in-hot-coflow) burner, which can produce MILD combustion regime in the upstream and conventional combustion regime in the downstream. CFD modeling method considering RANS equations and detailed reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…This simple definition has apparently built up a base for a great deal of research into MILD combustion in either premixed cases ,, or nonpremixed cases ,,,,,,,− since 2004. Both experimental ,,, ,,, , , and numerical ,,, , , investigations have been conducted for understanding of the MILD combustion characteristics, including its occurrence and development, as well as its ignition and stability.…”
Section: Definitions Of Mild Combustion and The Likementioning
confidence: 99%
See 1 more Smart Citation
“…This simple definition has apparently built up a base for a great deal of research into MILD combustion in either premixed cases ,, or nonpremixed cases ,,,,,,,− since 2004. Both experimental ,,, ,,, , , and numerical ,,, , , investigations have been conducted for understanding of the MILD combustion characteristics, including its occurrence and development, as well as its ignition and stability.…”
Section: Definitions Of Mild Combustion and The Likementioning
confidence: 99%
“…To improve our understanding of this combustion, a great deal of research work on its definition, ignition, evolution, and emissions has been conducted experimentally ,,− , ,,, ,,, , , and numerically. ,,, , ,,, , , In particular, the ch...…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the influences of CO 2 on the combustion characteristics of multidimensional flames has been studied in detail. The physical and chemical effects of CO 2 dilution on a CH 4 /H 2 jet flame in the MILD oxy-combustion regime have been investigated using two-dimensional numerical computations with a detailed kinetic mechanism (Tu et al, 2016;Tu et al, 2017). It was found that the chemical effects of CO 2 play a comparable role in the suppression of temperature rise to the physical effects (Tu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The influences of CO 2 dilution on the shape and structure of laminar CO/H 2 diffusion flames in an O 2 /N 2 /CO 2 coflow was examined (Xu et al, 2017), and the chemical effects of the thermal and transport properties of CO 2 on the flames were discussed in detail. The previous numerical studies provide important information on the effects of CO 2 under MILD (Tu et al, 2016;Tu et al, 2017) and syngas (Xu et al, 2017) combustion regimes. However, the effects of CO 2 on the flame shape and temperature distribution of gaseous-fuel-fired flames in an O 2 /CO 2 environment with a high O 2 concentration needs special attention and was not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Although the previous studies have revealed some significant features of MILD oxy-combustion, they were almost all conducted by numerical simulation using ideal physical models, ,, such as WSR, , counterflow flame, TFR, and open jet flame. ,, There has been some lack of experimental work for the MILD oxy-combustion, especially for H 2 O dilution. Moreover, to our best knowledge, the previous studies have never compared the in-furnace flame characteristics of MILD oxy-combustion under N 2 , CO 2 , and H 2 O dilutions over a relatively wide range of oxygen concentrations (from lean to rich oxygen) by experimental measurements and numerical simulations together.…”
Section: Introductionmentioning
confidence: 99%